2018
DOI: 10.1007/978-3-319-73915-1_36
|View full text |Cite
|
Sign up to set email alerts
|

Planar L-Drawings of Directed Graphs

Abstract: We study planar drawings of directed graphs in the L-drawing standard. We provide necessary conditions for the existence of these drawings and show that testing for the existence of a planar L-drawing is an NP-complete problem. Motivated by this result, we focus on upwardplanar L-drawings. We show that directed st-graphs admitting an upward-(resp. upward-rightward-) planar L-drawing are exactly those admitting a bitonic (resp. monotonically increasing) st-ordering. We give a lineartime algorithm that computes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…An L-drawing realizes a port assignment if each edge e = (v, w) is incident to the out(e)-port of v and to the in(e)-port of w. A port assignment admits a planar L-drawing if there is a planar L-drawing that realizes it. Given a port assignment it can be tested in linear time whether it admits a planar L-drawing [10].…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations
“…An L-drawing realizes a port assignment if each edge e = (v, w) is incident to the out(e)-port of v and to the in(e)-port of w. A port assignment admits a planar L-drawing if there is a planar L-drawing that realizes it. Given a port assignment it can be tested in linear time whether it admits a planar L-drawing [10].…”
Section: Preliminariesmentioning
confidence: 99%
“…Non-planar L-drawings were first defined by Angelini et al [1]. Chaplick et al [10] showed that it is NP-complete to decide whether a directed graph has a planar L-drawing if the embedding is not fixed. However it can be decided in linear time whether a planar st-graph has an upward-planar L-drawing, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A planar st-graph G is a bitonic st-graph if it admits a bitonic st-ordering. Deciding whether G is bitonic can be done in linear time both in the fixed [18] and in the variable [7] embedding settings. If G is not bitonic, every st-ordering σ of G contains a forbidden configuration defined as follows.…”
Section: Preliminariesmentioning
confidence: 99%